MENGGALI MATURITAS DIRI: KAJIAN METAFORA PADA LIRIK LAGU ALBUM RIUH - Azizah Suryani; Neneng Nurjanah (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2023)
This study examines the concept of self-maturity in the metaphor on the Riuh album created by Feby Putri by utilizing a qualitative approach using literature study techniques. The researcher focuses on the metaphors in Riuh's album through song lyrics which consist of ten songs. The data in this study is descriptive data that describes the concept of self-maturity in the metaphor of the song lyrics on the album 'Riuh'. The data source for this research is the verses in the song lyrics on the album 'Riuh'. The findings are 1) the researcher only took 4 different songs as research material, 2) there were 12 metaphorical data showing self-maturity in the lyrical verses studied